Xyloglucan-based hydrogel films for wound dressing: Structure-property relationships. (1st January 2018) - Ajovalasit, Alessia; Sabatino, Maria Antonietta; Todaro, Simona; Alessi, Sabina; Giacomazza, Daniela; Picone, Pasquale; Di Carlo, Marta; Dispenza, Clelia
Graphical abstract: Highlights: Xyloglucan-based crosslinked films with very high gel fractions are synthetized. PVA can be grafted to the network inducing high porosity and higher swelling degree. The addition of glycerol guarantees the desired flexibility. Films resulted non-cytotoxic and they do not release toxic components over 14 days. Abstract: Thin xyloglucan-based hydrogel films have been synthetized and characterized in the prospect of producing wound dressings. Polyvinyl alcohol (PVA) and glycerol (Gro) were added to have an optimal combination of softness, conformability and resilience. Physical hydrogels have been transformed into permanent covalent hydrogels by reaction with glutaraldehyde (GA). Network structure-process-property relationships are discussed on the account of the results of several complementary characterizations: FTIR, rheology, thermal analysis, morphological analysis, moisture retention and swelling measurements. Selected formulations were also subjected to preliminary in vitro cytotoxicity tests. The physical and mechanical properties of some of the xyloglucan-based hydrogel films produced, combined with absence of cytotoxicity, make them suitable candidates for integration with sensors to monitor the wound healing process and further biological investigations in animal models.